Peran Pengelolaan Peserta Didik dalam Mendukung Adaptasi Anak Usia Dini di Sekolah - Serly Herlina Amanda; Adelia Alfina Febriyani; Fetty Ernawati (CV. ITTC INDONESIA, 2026)
This study aims to analyze the role of student management in supporting early childhood adaptation in the school environment. The problem addressed is that many young children experience difficulties in adapting to a new school environment, such as lack of confidence, difficulty in social interaction, and inability to follow learning activities. This study uses a literature review approach by analyzing various journals and relevant scientific sources related to student management and early childhood adaptation. Data collection techniques were carried out through documentation studies of scientific articles obtained from various databases. The results show that effective student management through school programs such as habituation activities, school environment introduction, and group play activities plays an important role in supporting children's adaptation process. In addition, the role of teachers and the school environment are also supporting factors in creating comfort and readiness for children to learn. Therefore, effective student management can help early childhood adapt optimally in the school environment.